When Shakespeare met Raimi: David Mence’s Macbeth re-arisen (Altre Modernità, 2017)
What would happen if Macbeth returned as a zombie? David Mence's "Macbeth Re-Arisen", a daring sequel of Shakespeare's Macbeth, is the answer to that question. According to award-winning author David Mence, the borders between pulp science fiction, fantasy and horror and literary fiction are more permeable than we think (Mence, 2014). In his audacious "Macbeth Re-Arisen", entirely written in blank verse, Mence blends the medieval Scotland depicted by Shakespeare with the maniacal zombies of Sam Raimi's "Evil Dead" series. This article analyses the representation of zombies as characters in relation to David Mence's "Macbeth Re-Arisen", showing some continuity between this sequel of Shakespeares "Macbeth" and zombies in cinema, popular culture, and social studies. This article also analyses characters and topoi in ÒMacbeth Re-ArisenÓ and compares them to those in Shakesperare's "Macbeth".